2023
DOI: 10.3390/ijerph20065049
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Medical Nutrition Intervention on the Management of Hyperphosphatemia in Hemodialysis Patients with Stage 5 Chronic Kidney Disease: A Case Series

Abstract: The treatment and interdisciplinary management of patients with chronic kidney disease (CKD) continue to improve long-term outcomes. The medical nutrition intervention’s role is to establish a healthy diet plan for kidney protection, reach blood pressure and blood glucose goals, and prevent or delay health problems caused by kidney disease. Our study aims to report the effects of medical nutrition therapy—substituting foods rich in phosphorus-containing additives with ones low in phosphates content on phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Animal studies and clinical studies in CKD and dialysis patients have demonstrated that high dietary phosphate intake can induce negative effects by disrupting the tightly controlled endocrine regulation of phosphate. Table 1 summarizes key studies examining the consumption of a variety of market-available processed foods with the known addition of inorganic phosphate food additives [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Ultra-processed Food Cardiorenal Disease and Phosphate Addit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies and clinical studies in CKD and dialysis patients have demonstrated that high dietary phosphate intake can induce negative effects by disrupting the tightly controlled endocrine regulation of phosphate. Table 1 summarizes key studies examining the consumption of a variety of market-available processed foods with the known addition of inorganic phosphate food additives [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Ultra-processed Food Cardiorenal Disease and Phosphate Addit...mentioning
confidence: 99%
“…Moros , an E et al, 2023 [53] Dialysis patients treated with personalized nutrition therapy substituting processed high phosphate-additive foods with low phosphate-additive foods and use of phosphate binders significantly reduced phosphatemia after 60 days of treatment.…”
Section: Sullivan C Et Al 2009 [44]mentioning
confidence: 99%
“…T1DM remains a chronic disease associated with high morbidity [ 22 ], mortality, and a diminished work life [ 23 , 24 , 25 ]. When diabetes coexists with other diseases [ 26 , 27 , 28 , 29 , 30 , 31 ], the management of a patient’s condition is even more difficult.…”
Section: Introductionmentioning
confidence: 99%